Prevalence of chronic kidney disease in adults in England: comparison of nationally representative cross-sectional surveys from 2003 to 2016. Issue 8 (13th August 2020) - Hounkpatin, Hilda O; Harris, S; Fraser, Simon D S; Day, Julie; Mindell, Jennifer S; Taal, Maarten W; O'Donoghue, Donal; Roderick, Paul J
Abstract : Objectives: To identify recent trends in chronic kidney disease (CKD) prevalence in England and explore their association with changes in sociodemographic, behavioural and clinical factors. Design: Pooled cross-sectional analysis. Setting: Health Survey for England 2003, 2009/2010 combined and 2016. Participants: 17 663 individuals (aged 16+) living in private households. Primary and secondary outcome measures: Prevalence of estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m 2 and albuminuria (measured by albumin–creatinine ratio) during 2009/2010 and 2016 and trends in eGFR between 2003 and 2016. eGFR was estimated using serum creatinine Chronic Kidney Disease Epidemiology Collaboration and Modification of Diet in Renal Disease equations. Results: GFR <60 mL/min/1.73 m 2 prevalence was 7.7% (95% CI 7.1% to 8.4%), 7.0% (6.4% to 7.7%) and 7.3%(6.5% to 8.2%) in 2003, 2009/2010 and 2016, respectively. Albuminuria prevalence was 8.7% (8.1% to 9.5%) in 2009/2010 and 9.8% (8.7% to 10.9%) in 2016. Prevalence of CKD G1-5 (eGFR <60 mL/min/1.73 m 2 or albuminuria) was 12.6% (11.8% to 13.4%) in 2009/2010 and 13.9% (12.8% to 15.2%) in 2016. Prevalence of diabetes and obesity increased during 2003–2016 while prevalence of hypertension and smoking fell. The age-adjusted and gender-adjusted OR of eGFR <60 mL/min/1.73 m 2 for 2016 versus 2009/2010 was 0.99 (0.82 to 1.18) and fully adjusted OR was 1.13 (0.93 to 1.37). There was no significant period effect on the prevalence of albuminuria or CKD G1-5 from 2009/2010 to 2016 in age and gender or fully adjusted models. Conclusion: The fall in eGFR <60 mL/min/1.73 m 2 seen from 2003 to 2009/2010 did not continue to 2016. However, absolute CKD burden is likely to rise with population growth and ageing, particularly if diabetes prevalence continues to increase. This highlights the need for greater CKD prevention efforts and continued surveillance.